"Let me take a selfie." Motives for posting electronic word-of-mouth in visual content on Instagram - Anna Margrét Gunnarsdóttir 1987- (2014)
Word-of-mouth has been a part of discussions since human beings began communicating with others. With the outburst of social media services people are constantly communicating online. The concept of word-of-mouth has branched into cyberspace and is known in that context as electronic word-of-mouth. An online photo-sharing application called Instagram has in a few years become one of the most popular social mediums, with 200 million users worldwide. Instagram users show many signs of being particularly inclined to electronic word-of-mouth behaviour making it an interesting topic of research. A quantitative study was conducted within a sample of Instagram users in Iceland. The objective of the study was to understand why and how people use Instagram as a word-of-mouth medium. The main conclusion is that Instagram displays all the characteristics of an electronic word-of-mouth medium. The study’s results show that its users mainly like to see other users photos and that they mostly share photos of either friends and family or experiences and events. On a level of product visibility, Instagram users mostly share photos of products they are happy with and with the intention of assisting their followers in making good purchasing decisions. Given its emphasis on visual content, Instagram is a feasible option for companies to optimize their online presence and their relationship with consumers.